2015
DOI: 10.3389/fnhum.2015.00018
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment and predicting outcomes in patients with depressive symptoms: a review of potential role of peripheral blood based biomarkers

Abstract: Depression is one of the major global health challenges and a leading contributor of health related disability and costs. Depression is a heterogeneous disorder and current methods for assessing its severity in clinical practice rely on symptom count, however this approach is unreliable and inconsistent. The clinical evaluation of depressive symptoms is particularly challenging in primary care, where the majority of patients with depression are managed, due to the presence of co-morbidities. Current methods fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 77 publications
0
15
0
3
Order By: Relevance
“…8 Evidence suggests that factors associated with the inflammatory process, neurotransmission, neurotrophy, neuroendocrine and metabolic systems could be used to recognize the mechanism of disease for individuals suffering from depression. 9 The biological markers for understanding the pathophysiology of MDD are rare, and although there are few risk assessment factors, the findings are largely inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…8 Evidence suggests that factors associated with the inflammatory process, neurotransmission, neurotrophy, neuroendocrine and metabolic systems could be used to recognize the mechanism of disease for individuals suffering from depression. 9 The biological markers for understanding the pathophysiology of MDD are rare, and although there are few risk assessment factors, the findings are largely inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…19 The evidence to date suggests that markers reflecting the activity of inflammatory, neurotransmitter, neurotrophic, neuroendocrine and metabolic systems may be able to predict mental and physical health outcomes in currently depressed individuals, but there is much inconsistency between findings. 20 In this review, we focus on these five biologic systems.…”
Section: Biomarkers: Systems and Sourcesmentioning
confidence: 99%
“…Moreover, animal studies have demonstrated that various classes of antidepressants can reduce levels of oxidative stress markers (Eren et al, 2007a , b ; Maes et al, 2011a ; Leonard and Maes, 2012 ), increase several endogenous antioxidants (Maes et al, 2011a ) and also decrease the periodontal disease severity (Branco-de-Almeida et al, 2012 ; Aguiar et al, 2013 ; Galli et al, 2013 ). Captivatingly, these biological processes have been revealed to participate to the aetiology of depression and periodontal disease co-morbidities, as well, and thus may represent a bridge between these pathologies (Maes et al, 2011b ; Bullon et al, 2014 ; Rossetti et al, 2014 ; Jani et al, 2015 ; Kang et al, 2015 ). Changes in health-related behaviors , such as oral hygiene, smoking, diet, alcohol consumption that occurs in depressed patients can also be related to the occurrence of periodontal disease (Kurer et al, 1995 ; D'Alessandro et al, 2014 ; Peltzer and Pengpid, 2014 ; Yuen et al, 2014 ; Alkan et al, 2015 ).…”
Section: Depression As a Cause Of Periodontal Diseasementioning
confidence: 99%